Identification of Neuritin 1 as a local metabolic regulator of brown adipose tissue - Sánchez-Feutrie, Manuela; Romero, Montserrat; Veiga, Sónia R.; Borràs-Ferré, Núria; Berrow, Nick; Ràfols, Martina; Giménez, Noemí; Rodgers-Furones, Andrea; Sabaté-Pérez, Alba; Rodríguez Pérez, Ángela; Cataldo, Luis Rodrigo ; 0000-0003-1225-414X; Burghardt, Hans; et al. (Nature Communications, 2025)
Brown adipose tissue (BAT) plays a key role in metabolic homeostasis through its thermogenic effects and the secretion of regulatory molecules. Here we report that RAP250 haploinsufficiency stimulates BAT in mice, thus contributing to a decrease in fat accumulation. Local in vivo AAV-mediated RAP250 silencing in BAT reduces body weight and fat mass and enhances glucose oxidation, thereby indicating that RAP250 participates in the regulation of BAT metabolic activity. Analysis of the mechanisms led to the finding that Neuritin 1 is produced and released by brown adipocytes, it plays a key metabolic role, and it participates in the enhanced BAT metabolic activity under RAP250 deficiency. Forced overexpression of Neuritin 1 in UCP1-expressing cells markedly decreases fat mass and body weight gain in mice and induces the expression of thermogenic genes in BAT. Neuritin 1-deficient brown adipocytes also shows a reduced β-adrenergic response. We demonstrate a metabolic role of BAT-derived Neuritin 1 acting through an autocrine/paracrine mechanism. Based on our results, Neuritin-1 emerges as a potential target for the treatment of metabolic disorders.